Layer-dependent electronic and magnetic properties of two-dimensional graphitic molybdenum carbide - Wang, Hao (2024)
Intrinsic magnetic two-dimensional (2D) materials with high critical temperature are highly desired in advanced spintronics applications. Via first-principles calculations, we firstly predict that two-dimensional molybdenum carbide (with a chemical formula of Mo2C12) monolayer is a highly stable antiferromagnetic (AFM) semiconductor with a band gap around 1 eV and a high Néel temperature of 420 K. We then show that the multilayer (Mo2C12)n, where n is the number of layers, exhibits interesting electronic and magnetic properties that are sensitively dependent on the number of layers. The stability of the AFM configuration and the energy gap rapidly decrease with the number of layers. When n≤5, (Mo2C12)n remains AFM, while magnetic moments are mainly located on surface Mo atoms, and Mo atoms on top and bottom surfaces have opposite spin polarizations. When n>5, the AFM phase is unstable and the material becomes metallic. These layer-tunable properties make (Mo2C12)n potentially useful for various electronics and spintronics applications. As one example, an intriguing (Mo2C12)5 based magnetic metal–semiconductor–metal heterojunction is proposed in this work.